DEVELOPMENT OF MECHANISMS FOR SOCIO-ECONOMIC DEVELOPMENT OF REGIONS IN CRISIS CONDITIONS - GONTA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study revealed the relevance of ensuring the socio-economic development of regions. The main mechanisms of socio-economic development of the regions are proposed, which will make it possible to prevent a crisis in the future. The toolkit of research and the assignment of concepts and theories regarding the provision of socio-economic development of regions is presented. the main methods that make it possible to study the development of regions are given. The analysis of the researched tools is one of the theoretically and practically significant problems of the transformation period. In order to develop the mechanisms of socio-economic development of regions, it is necessary to be guided by the tools that can be used by state administration bodies of different levels to influence individual regions or the entire regional national economy. The long-term effectiveness of such an analysis largely depends on the adequacy of the reflection of the target priorities of the economic development of this region, which reflect, in turn, the strategy of its economic development. It has been proven that ensuring stable socio-economic development pursues the achievement of certain goals set at the national or regional levels, so it is natural to ask the question about the effectiveness of the conducted up to now on the existing definitions of the crisis. So, the mechanisms of socio-economic development should be considered as a system focused on the combination of two goals: achieving the maximum development of each of the regions and striving to smooth out the high levels of diversification of the regions.
Keywords: socio-economic development; region; mechanism; regional management